Cultural Competition and Collaboration of Confessions in Lithuania Minor in the First Half of the Eighteenth Century: Impulses for Lithuanian Writing - Aleknavičienė, Ona (Senoji Lietuvos literatūra, 2018)
The article aims at the analysis of confessional competition between traditional Evangelical Lutherans, or Orthodox Lutherans, and Pietists that took place from the second to the fourth decades of the eighteenth century in Lithuania Minor. Emphasis is placed on the impulses for Lithuanian writing that were stimulated by this competition. The article focuses on (1) how the competition between Evangelical Lutherans and the Pietists developed, (2) what the forms of their collaboration were, and (3) what effect this competition and collaboration had on the evolution of Lithuanian writing and on the culture of Lithuania Minor. This is shown through two distinct examples of activities of Pietist Heinrich Lysius (1670–1731) and Orthodox Lutheran Johann Behrendt (1667–1739), which ensued in the environment of intense competition and collaboration. In the context of confessional competition and collaboration, two centres stand out in the literary and cultural life of the first half of the eighteenth century: Halle, the Pietists’ centre, and Karaliaučius (Königsberg), the centre of Pietists and Orthodox Lutherans. In Lithuania Minor, the educational reform and publication of Lithuanian books associated with it was initially undertaken by the Pietists who from 1718 to 1721 were led by Heinrich Lysius, a church and school inspector, a professor at Königsberg University, and an assessor of Semba consistory. Later the initiative was taken over by the Orthodox Lutherans unified by Johann Jacob Quandt, also a professor at Königsberg University, who was also the senior court preacher, an assessor and superintendant general of Semba consistory. Heinrich Lysius’s letters to August Hermann Francke written from 1718 to 1721, Francke’s diaries and information in the periodical press point to intensive collaboration between the Pietists of Halle and Königsberg in implementing orders issued by Friedrich Wilhelm I of Prussia, in particular those concerning the training of teachers and pastors for Lithuanian parishes. Although Lysius, who was not of local descent, could not rally Lithuanian pastors for long-term work (they opposed demanding requirements for pastors and the policy of language use; also, the funds for the implementation of the foreseen plans were insufficient), his activities had some positive outcomes: (a) the manuscript of Luther’s Small Catechism (1719) was prepared under his guidance, and (b) the Lithuanian language seminar was established at Königsberg University in 1718. The period of the 1720s–1730s was especially productive for Lithuanian literature. The demand for teaching literature that arose in the process of the development of the system of obligatory primary education encouraged initiative on both sides. Orthodox Lutherans initially published Luther’s Small Catechism prepared under Lysius’s guidance (1722, 1726, 1730, etc.). A translation of Johann Anastasius Freylinghausen’s treatise Ordnung des Heyls – Dawádnas Mókslas apie Dußiôs Ißgánimą (1729; 1735) – prepared by the participants of the Lithuanian language seminar at the University of Halle, the dictionary Vocabvlarivm Litthvanico-Germanicvm, et Germanico-Litthvanicum (1730) by the seminar dozent Friedrich Wilhelm Haack, and later two editions of Fabian Ulrich Glaser’s hymnal Kélos Nobaźnos Giesmes (1736, 1738) were all published in Halle. In this way Halle became a centre for the teaching of the Lithuanian language (the Lithuanian language seminar functioned from 1727 to 1740) and for preparation and publication of Lithuanian Pietist literature. Orthodox Lutherans prepared the New Testament (1727), the Book of Psalms (1728), agenda Dawádnas Pamokinnimas (1730), the hymnal Iß naujo pérweizdėtos ir pagérintos Giesmû-Knygos (1732), and the complete Bible (1735). All these books were published in Königsberg. The letter of 20 March 1729 of Johann Behrendt, Bishop of Įsrutis (Insterburg), to Gotthilf August Francke shows that the confrontation between the Pietists of Halle and the Orthodox Lutherans of Lithuania Minor was not strong, because (a) requested by Gotthilf August Francke, the head of the seminar of the Lithuanian language in Halle, Behrendt edited the translation of Johann Anastasius Freylinghausen’s treatise Dawádnas Mókslas apie Dußiôs Ißgánimą by the seminar participants (1729); b) requested by Francke, he translated the prayer from the above treatise ‘Maldéle kurre Jaunieji / prie Spawedês eidami sakyti gál’ (‘Gebetlein / welches von der Jugend an statt einer Beicht gebrauchet werden mag’) into Lithuanian. Participants of the Lithuanian language seminar in Halle had also translated August Hermann Francke’s programmatic treatise Die Lehre Vom Anfang Christliches Lebens into Lithuanian, but there is no information regarding its publication. Lithuanian translations of two prayers from this treatise were included in Freylinghausen’s treatise Dawádnas Mókslas apie Dußiôs Ißgánimą: (a) ‘Malda dienißka. Rytmeczeis skaitoma’ (‘Ein tägliher Morgen=Seegen’); (b) ‘Malda dienißka. Wakarais skaitoma’ (‘Ein tägliher Abend=Segen’). A broad information and communication network created prerequisites for successful activities of the Pietists of Halle and those of Lithuania Minor. Maintenance of regular contacts consolidated motivation for joint work and provided a strong impetus for the culture of Lithuania Minor by stimulating the development of churches and of the whole system of education. The fact that the Pietists were looking for contacts with Orthodox Lutherans shows that they avoided confessional and territorial insularity. Cultural competition between Orthodox Lutherans and Pietists of the first half of the eighteenth century was constructive: numerous processes point to an action and a subsequent counteraction. Therefore an evaluation of literary and cultural processes should take into account not only the merits of one particular side, but also the steps made by one side that resulted in steps taken by the other side.